2015
DOI: 10.3906/sag-1402-124
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of hypermetabolic mediastinal–hilar lymph nodes determined byPET/CT in pulmonary and extrapulmonary malignancies: correlation with EBUS-TBNA

Abstract: Background/aim: We aimed to define the optimal SUVmax cut-off value in determination of mediastinal-hilar lymph node metastasis, by comparing positive PET/CT results with the results of endobronchial ultrasound guided transbronchial needle aspiration biopsy (EBUS-TBNA).Materials and methods: Thirty-one patients with malignancy whose PET/CT imaging revealed a hypermetabolic mediastinal and/ or hilar lymph node and who had undergone EBUS-TBNA were evaluated retrospectively. Histopathology was regarded as the gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Increased 2‐fluoro‐2‐deoxy‐ d ‐glucose uptake on positron emission tomography (PET) is fairly sensitive for metastases (~65%) . However, a significant proportion of infectious and inflammatory diseases also show increased PET uptake, lowering its specificity (~35%) and diagnostic accuracy (~65%) for malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…Increased 2‐fluoro‐2‐deoxy‐ d ‐glucose uptake on positron emission tomography (PET) is fairly sensitive for metastases (~65%) . However, a significant proportion of infectious and inflammatory diseases also show increased PET uptake, lowering its specificity (~35%) and diagnostic accuracy (~65%) for malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of our study include its retrospective single centre nature with a limited sample size, but this compares well with the numbers reported in other studies (31 in the study reported by Kandemir et al). [ 4 ] We could not confirm the reactive lymphadenitis diagnoses with mediastinoscopy, as patients were not willing for more invasive surgical procedures, which is a common observation in malignancy situations. Our numbers are skewed towards benign diagnoses, but this is an important feature to highlight in an endemic tuberculosis situation, which is common in many parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…In ETM, a SUV value of ≥6.3 and above is considered malignant, with sensitivity and specificity of 70.6% and 83.3%, respectively. [ 4 ] An accurate tissue diagnoses of PET–positive MLN is vital, for initial staging of primary thoracic or extra-thoracic malignancy or detect recurrence in patients with treated malignancy. However, in PET HM-MLN, there is the confounding possibility of benign disease with inflammatory activity leading to a false-positive high SUV simulating malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, the Nomenclature Committee of the International Union of Biochemistry defined GGN as a fuzzy density where the bronchi or lung blood vessels remain visible with high-resolution CT (11). Additionally, it refers to a class of non-specific CT signs that have a slightly increased density in high-resolution CT images (12). With regard to pathology, GGN has been identified for a variety of inflammatory conditions, edema, bleeding, fibrosis and tumor lesions (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%